Stem and leaf growth rates define the leaf size vs. number trade-off - Sun, Jun (AoB Plants, 2019)
The trade-off between leaf number and individual leaf size on current-year shoots (twigs) is crucial to light interception and thus net carbon gain. However, a theoretical basis for understanding this trade-off remains elusive. Here, we argue that this trade-off emerges directly from the relationship between annual growth in leaf and stem mass, a hypothesis that predicts that maximum individual leaf size (i.e. leaf mass, M(max), or leaf area, A(max)) will scale negatively and isometrically with leafing intensity (i.e. leaf number per unit stem mass, per unit stem volume or per stem cross-sectional area). We tested this hypothesis by analysing the twigs of 64 species inhabiting three different forest communities along an elevation gradient using standardized major axis (SMA) analyses. Across species, maximum individual leaf size (M(max), A(max)) scaled isometrically with respect to leafing intensity; the scaling constants between maximum leaf size and leafing intensity (based on stem cross-sectional area) differed significantly among the three forests. Therefore, our hypothesis successfully predicts a scaling relationship between maximum individual leaf size and leafing intensity, and provides a general explanation for the leaf size-number trade-off as a consequence of mechanical-hydraulic constraints on stem and leaf growth per year.